The Relationship between Fear of Falling and Level of Education and Living Style in the Elderly - Mahyar Salavati; Hamzeh Baharlouei; Behnam Akhbari (Vesnu Publications, 2016)
Introduction: This study evaluated the relationship between fear of falling, and the level of education and the living style of Iranian elderly. Materials and Methods: This was a descriptive-analytical study on 191 elderly living in the community and nursing homes. The participants were selected through simple non-probability sampling. The fear of falling, level of education, and living style were determined using a multiple choice questionnaire and the relationship between was studied. The Kruskal-Wallis test and Spearman correlation coefficient were used for statistical analysis. Results: The results of Kruskal-Wallis test showed no significant difference between individuals with different life styles in terms of fear of falling (P = 0.25).The Spearman correlation coefficient also showed no significant relationship between fear of falling and educational level (P = 0.32, r = 0.07). Conclusion: This study results showed that there is no relationship between fear of falling, and education level and living style in Iranian elderly.